PENGARUH KEPEMIMPINAN, MANAJEMEN PENGETAHUAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. PELABUHAN INDONESIA (PERSERO) I CABANG KOTA DUMAI - Teguh Pambudi; Dewita Suryati Ningsih; Taufiqurrahman ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in the Dumai City. The purpose of this study was to determine the influence leadership, knowledge management and organizational culture to performance. population of this research are 171 employees at the PT. Pelabuhan Indonesia (PERSERO) I Dumai city branch. Research variables used are leadership, knowledge management and organizational culture as independent variables and the employees performance as the dependent variable. Methods of data analysis using linear regression analysis Descriptive assisted by SPSS 21 for windows. The results of this study concluded that leadership, knowledge management and organizational culture a positive and significant effect on employees performance. The coefficient of determination employee performance Test Results obtained 0.740, which means that leadership, knowledge management and organizational culture contributes influence on the dependent variable for 74%, while the remaining 26% is influenced by other variables not included in the. The expectation researcher for this research is the company should to improve factor of leadership, Knowledge Management and organization culture as it has a significant role in improving the performance of employees.Keyword : Leadership, Knowledge Management, Organizational Culture and Employees Performance